Evaluation of humoral and cellular response to third dose of BNT162b2 mRNA COVID-19 vaccine in patients treated with B-cell depleting therapy. Issue 131 (July 2022) - Firinu, Davide; Fenu, Giuseppe; Sanna, Giuseppina; Costanzo, Giulia A.; Perra, Andrea; Campagna, Marcello; Littera, Roberto; Locci, Carlotta; Marongiu, Alessandra; Cappai, Riccardo; Melis, Maurizio; Orrù, Germano; et al.
Abstract: Objective: to investigate the responses to mRNA COVID-19 vaccines in a cohort of immunosuppressed patients affected by immune-mediated inflammatory diseases (IMID). Methods: we have measured humoral and cellular immunity using quantitative IgG anti-SARS-CoV-2 Spike antibody (anti-S-IgG), neutralization assays and specific interferon-gamma (IFN-g) release assay (IGRA) before and after the third dose of BNT162b2. The response of those on anti-CD20 (n = 18) was then compared with healthy controls (HC, n = 18) and IMID naïve to anti-CD20 drugs (n = 13). Results: a third BNT162b2 dose is highly immunogenic in IMID patients naïve to anti-CD20, as 100% of the subjects seroconverted compared to the 55% in anti-CD20. The rate of IGRA response was of 79% in anti-CD20, 50% in IMID naïve to anti-CD20, 100% in HC. Among those who have seroconverted, IMID patients had significantly reduced anti-S-IgG and neutralization titers compared to HC, whereas no significant difference was observed when comparing anti-CD20 and HC. Furthermore, 13% of anti-CD20 and 7.7% of IMID were simultaneously negative for both neutralizing antibodies and IGRA after three doses. Conclusion: these data draw attention to the immunogenicity of COVID-19 vaccination in treated IMID, taking specific groups into consideration for vaccination program. Highlights: We measured humoral and cellular immunity before and after the 3rd dose of BNT162b2. We analysed patients treated with anti-CD20, patients immunosuppressed and controls. Anti-spike IgG and PRNT90 neutralization assay and IGRA to SARS-CoV-2 were performed. The rate of seroconversion for those in anti-CD20 is slightly improved by 3rd dose. Cellular response to 3rd dose is high among anti-CD20 and reduced in anti-CD20 naïve.